Efforts to Improve Learning Outcomes of Bullet Repellent Skills in Elementary School Students With Tail Ball Action Modifications - Abi Zahed Al Qurtubi; Ali Munir; Carles Nyoman Wali (Edumaspul: Jurnal Pendidikan, 2022)
The sport of shot put is one of the athletic disciplines of the number throw. Bullet repulsion in general uses round-shaped iron with sizes that vary from 2kg to 7kg. This study aims to improve student learning outcomes on bullet repellent by using modified ball rope aids. This research was conducted at Margomulyo Ngawi State Elementary School 1. This study involved all grade V students with a total of 25 teriri students from 11 men and 14 women. The method used in this study is Classroom Action Research with data collection techniques through observation and test. The study was carried out using two cycles. In the first cycle, students who completed 11 (44%) while those who were not completed were 14 (56%) students with an average score of 65. In cycle II there was a significant increase in overall learning outcomes 25 (100%) students had completed learning with an average score of 86. Based on these results, it was proven that the use of ball rope modifications can improve student learning outcomes in bullet repellent material.